Beware of the persistent abscess: Chronic granulomatous disease presenting with suppurative lymphadenitis - C. Pardy; J. Pumphrey; R. Hallows; V. Scott; K. Fidler (Elsevier, 2016)
An 18-month old boy presented with axillary suppurative lymphadenitis, which failed to respond to conservative management. His care was transferred to pediatric surgeons for further management. Resolution of the abscess was not achieved despite two incision and drainage procedures. Cultures obtained from the abscess grew Serratia Marcescens, and Staphylococcus aureus. A diagnosis of chronic granulomatous disease (CGD) was made, subsequently identified to be x-linked. Review of a chest X-ray previously reported as normal identified focal consolidation. This was investigated with CT and thought to represent previous granuloma with current Staphylococcus infection. The boy was started on prophylactic septrin and itraconizole, in addition to 2 months of treatment antibiotics. The abscess healed, and a repeat CT demonstrated resolution of the cavitating lung lesion. A gastrostomy was inserted in preparation for a T cell-depleted haploidentical bone marrow transplantation, which to date appears to have been curative. Chronic granulomatous disease is a rare genetic primary immunodeficiency associated with high mortality if diagnosis is delayed. The recent establishment of a UK CGD registry has identified a far higher prevalence than previously thought. Stem cell transplantation now offers a potentially curative treatment, with better outcomes in younger children. It is therefore essential that pediatric surgeons are aware of this diagnosis, and that appropriate investigations are instituted when an abscess fails to resolve, or has cultured unusual organisms.